Exploring Chinese EFL Learners' Achievement Emotions and Their Antecedents in an Online English Learning Environment - Yang, Yingli; Gao, Zihan; Han, Yawen (Frontiers in Psychology, 2021)
Drawing on the control-value theory, this study adopted a qualitative approach to explore the various achievement emotions Chinese EFL learners experienced in an online English learning environment and their antecedents during the COVID-19 pandemic period. Data were collected from six Chinese EFL students through semi-structured interviews and reflective journals supplemented with their class notes. Thematic analysis was performed using the qualitative data management software NVivo 12 plus. Results showed that the students experienced diverse emotions such as enjoyment, relaxation, anxiety, guilt, boredom and helplessness. Apart from the environmental antecedents of teacher and peer factors and individual antecedents of control-value appraisals, four novel antecedents were identified which had influence on emotions experienced in the online learning context, including environmental antecedents of internet connection and workload outside classroom, as well as the individual antecedents of students’ self-regulation of learning behavior and learning environment.